Linha M: marcador anatômico para o óstio do seio maxilar - Leite, Janaina Gonçalves da Silva (2020)
The difficulty in visualizing the maxillary sinus ostium (MSO), even with angled optics, may result in the lack of inclusion of the ostium, an important cause of failure in endoscopic sinus surgery. As such, an anatomical landmark to locate the ostium could reduce residual or recurrent disease. The M line is an imaginary horizontal marker, parallel to the nasal cavity floor, extending from the lower portion of the ethmoidal bulla to the uncinate process. This study aimed to determine if the M line can identify the MSO during endoscopic sinus surgery. Dissections were performed in 57 cadavers (n=114) and 73 computed tomography scans (n=146) of patients with chronic rhinitis or rhinosinusitis were examined. Next, the M line was applied in the endoscopic sinus surgery of five patients. It crossed the MSO in 112 dissected sides (98%) and 140 sides on computed tomography scans (96%) and was used to identify the MSO in all operated patients, without complications during or after surgery. The M line is an anatomical landmark that indicates the location of the MSO and could therefore help endoscopic sinus surgery be more effective, safe and minimally invasive.